Sustainable Solutions: Holistic Strategies For Electric Vehicle Adoption And Transportation Sustainability (Journal of Namibian Studies : History Politics Culture, 2023)
This research provides a thorough examination of marketing techniques in the electric vehicle (EV) business, utilizing several bibliometric indicators, trends in author productivity, and country-specific data. The data reveals an apparent rise in research focus and the influence of citations around the year 2020, followed by a subsequent decrease in future years. It also examines the specific effects of different sources, highlighting the significant influence of scholarly journals like the "Journal of Power Sources" and "Sustainability (Switzerland)" in shaping discussions around electric vehicle marketing. The analysis of commonly appearing terms and networks of word associations uncovers essential research topics like marketing tactics, sustainability, business trends, and consumer conduct. Our report provides useful insights into the changing landscape of EV market research and suggests future directions for both scholars and practitioners. Our goal is to provide a clear guide for understanding and navigating the complex world of EV marketing. We emphasize the importance of considering multiple disciplines and recommend comprehensive tactics to promote the adoption of EVs and develop sustainable transportation solutions.